A Lexical Analysis of the Bersih Desa Tradition in Jatisumber: Sustaining Ancestral Heritage in Mojokerto Regency - Nabila Purnamasari; Millatuz Zakiyah (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study examines the meaning of offerings in the village clean tradition in Jatisumber Mojokerto. This research uses a linguistic anthropology approach by utilizing semiotic theory. Data was obtained from the management of the clean tradition of Jatisumber village and cultural experts in Jatisumber and then analyzed using the Lyons meaning triangle. The results of the study showed that there were twenty-one offerings that could be classified based on form: produce, food, drinks, fragrances, and equipment. Overall, the meaning of the offering in this tradition is that in living a life, humans must always be grateful to God Almighty, maintain good relations with nature, ancestors, and others. By doing this, it is hoped that their lives will be prosperous, unhindered, and protected from all dangers. The strategy of naming and interpreting offerings is based on three things, namely (1) signs, an acronym for the philosophical concept or meaning to be achieved, (2) significatum that represents the philosophical concept or meaning to be achieved, and (3) concept or philosophical meaning to be achieved in accordance with the function of the sign.